Design and Validation of The Encyclopedia of Plant Morphology and Anatomy of The Zingiberaceae Family as a Learning Resource for High School Biology - Tanriati Tanriati; Hilda Karim; Syamsiah Syamsiah (Universitas Negeri Makassar, 2026)
AbstractPurpose: This study aimed to develop and validate an encyclopedia of morphology and anatomy of plants belonging to the Zingiberaceae family as a learning resource for senior high school biology.Research Methodology: This research was conducted at the Biology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Makassar. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The developed product was an encyclopedia containing information on the morphological and anatomical characteristics of Zingiberaceae plants. Product validity was evaluated by two expert validators using validation instruments and analyzed with the Gregory validity technique.Results: The validation results showed that the encyclopedia obtained a Gregory validity coefficient of 1.00, indicating a very high validity level. All assessment aspects, including content, language, presentation, and graphics, received maximum scores from both validators, demonstrating strong agreement regarding the quality and feasibility of the product.Conclusions: The encyclopedia is valid and suitable for use without revision as a biology learning resource for senior high school students. It provides contextual and locally based learning materials supported by morphological and anatomical documentation.Limitations: The encyclopedia only covers 10 species of the Zingiberaceae family, and some anatomical structures were not optimally visible because the documentation used fresh preparations.Contributions: This study contributes to biology education by providing a valid learning resource based on local plant diversity that can support the teaching and learning of plant morphology, anatomy, and biodiversity in senior high schools.Keywords : Plant Anatomy, ADDIE Model, Morphology and Learning Resources